Coast : A Celebration of Britain's Coastal Heritage - Somerville, Christopher; Foreword by Crane, Nicholas (London BBC Books, 2005)
Accompanying the "BBC" series, this book celebrates Britain's coastal areas and serves as a practical guide to almost all that they have to offer. Divided into the 12 coastal regions, it presents a region-by-region reference of places, people, activities, natural history, historic events and interesting facts.
Include Color Illustrations, Maps and Index.
A Celebration of Britain's Coastal Heritage.
Keywords: Great Britain -- Coasts